(untitled) (Oratio Directa, 2024)
This study discusses the corruption case involving bribery and gratuities for mining business permits (IUP) committed by Mardani H. Maming in Tanah Bumbu Regency. The Corruption Eradication Commission (KPK) arrested him for allegedly receiving Rp104.3 billion. The study uses mass-media reality-construction theory, a qualitative framing-analysis approach, a constructivist paradigm, media-text analysis, descriptive research, and documentation as its data-collection technique. The findings show how media organizations or journalists frame news events from their respective perspectives, thereby revealing the social construction, neutrality, and factuality of the coverage produced by Tempo.co and Suara.com. The study concludes that both media should continue to maintain news elements in accordance with Law No. 40 of 1999 concerning the Press and the Journalistic Code of Ethics.